Artificial Intelligence: Way Forward for India - Sunil Kumar Srivastava (IAES International Journal of Artificial Intelligence (IJ-AI), 2018)
Artificial Intelligence (AI) is likely to transform the way we live and work. Due to its high potential, its adoption is being treated as the fourth industrial revolution. As with any major advancement in technology, it brings with it a spectrum of opportunities as well as challenges. On one hand, several applications have been developed or under development with potential to improve the quality of life significantly. As per a study, it is expected to double the annual economic growth rate of 12 developed countries by 2035. On the other hand, there is a possibility of loss of jobs. As per the available reports, the loss of jobs during the next 10-20 years is estimated to be 47% in the US, 35% in the UK, 49% in Japan, 40% in Australia, and 54% in the EU. In the era of globalization, no country can isolate itself from the impact of the advances in technology. However, the benefits can be maximized and losses can be minimized by putting necessary infrastructure and policy in place. Though several countries have decided their strategy for AI, India has not yet formulated its strategy. The report reviews the international as well as national scenario and suggests way forward for India.